The Arabidopsis thaliana–Fusarium oxysporum strain 5176 pathosystem: an overview. (16th July 2022) - Wang, Liu; Calabria, Jacob; Chen, Hsiang-Wen; Somssich, Marc
Abstract : This review provides an overview of the advances made with the Arabidopsis thaliana – Fusarium oxysporum 5176 pathosystem in understanding the cause and defense against wilt disease in plants. Abstract: Fusarium oxysporum is a soil-borne fungal pathogen of several major food crops. Research on understanding the molecular details of fungal infection and the plant's defense mechanisms against this pathogen has long focused mainly on the tomato-infecting F. oxysporum strains and their specific host plant. However, in recent years, the Arabidopsis thaliana – Fusarium oxysporum strain 5176 ( Fo 5176) pathosystem has additionally been established to study this plant–pathogen interaction with all the molecular biology, genetic, and genomic tools available for the A. thaliana model system. Work on this system has since produced several new insights, especially with regards to the role of phytohormones involved in the plant's defense response, and the receptor proteins and peptide ligands involved in pathogen detection. Furthermore, work with the pathogenic strain Fo 5176 and the related endophytic strain Fo 47 has demonstrated the suitability of this system for comparative studies of the plant's specific responses to general microbe- or pathogen-associated molecular patterns. In this review, we highlight the advantages of this specific pathosystem, summarize the advances made in studying the molecular details of this plant–fungus interaction, and point out open questions that remain to be answered.